LIGHTWEIGHT VERSION FOR DIGITAL QURAN MODEL BY HANDLING DUPLICATION - Md Norwawi, Norita; Mohammad Alomoush, Ashraf Saleh (PERINTIS eJournal, 2023)
Digital Quran may be implemented as image-based, text-based, audio, or video based. In terms of storage, the compilation of Quranic verses in images, audio, or video will consume ample storage space. On the other hand, the digital Quran in text-based format benefitted the Hexadecimal representation due to the use of Unicode. However, space was not optimized due to the string concatenation approach of the Unicode of each letter that occurs in a particular Quranic word. Thus, with the Unicode representation, the storage size is directly proportional to the length of a word. This paper presents a new Digital Quran Model (DQM) that aims to reduce storage requirements through individual word conversion into Hexadecimal instead of combining letter sequences. Due to the repetitive nature of Quran words, space usage can be further improved by handling Quranic word duplication. DQM was implemented using Visual Studio and Java servers. The solution quality was measured by comparing the file size before and after applying the DQM model. For example, space reduction for surah Al-Fatihah is 46.91%. The outcome helps the researchers to develop a lightweight Digital Quran application that users can benefit from due to its reliability, validity, and storage management efficiency and thus can be used as a standard application.